Impact of Repetitive Transcranial Magnetic Stimulation on Neurocognition and Oxidative Stress in Relapsing-Remitting Multiple Sclerosis: A Case Report - Agüera, Eduardo; Caballero-Villarraso, Javier; Feijóo, Montserrat; Escribano, Begoña M.; Bahamonde, María C.; Conde, Cristina; Galván, Alberto; Túnez, Isaac (Frontiers in Neurology, 2020)
Multiple sclerosis (MS) is a neurodegenerative condition whose manifestation and clinical evolution can present themselves in very different ways. Analogously, its treatment has to be personalized and the patient's response may be idiosyncratic. At this moment there is no cure for it, in addition to its clinical course sometimes being torpid, with a poor response to any treatment. However, Transcranial Magnetic Stimulation (TMS) has demonstrated its usefulness as a non-invasive therapeutic tool for the treatment of some psychiatric and neurodegenerative diseases. Some studies show that the application of rTMS implies improvement in patients with MS at various levels, but the effects at the psychometric level and the redox profile in blood have never been studied before, despite the fact that both aspects have been related to the severity of MS and its evolution. Here we present the case of a woman diagnosed with relapsing-remitting multiple sclerosis (RRMS) at the age of 33, with a rapid progression of her illness and a poor response to different treatments previously prescribed for 9 years. In view of the patient's clinical course, a compassionate treatment with rTMS for 1 year was proposed. Starting from the fourth month of treatment, when reviewing the status of her disease, the patient denoted a clear improvement at different levels. There followed out psychometric evaluations and blood analyses, that showed both an improvement in her neuropsychological functions and a reduction in oxidative stress in plasma, in correspondence with therTMS treatment.